Optimization of soil ph by using calcium carbonate from shell waste / Nur Aain Ab Aziz - Ab Aziz, Nur Aain (Faculty of Applied Sciences, 2016)
Calcium carbonate (CaC03) is an alternative way to optimize the soil pH. In this study, calcium carbonate from shell waste has been used at different weight loading in order to investigate the effects of calcium carbonate on the soil pH and different types of soil have been used during this study. Characterization of CaC03 has been done by using FTIR and TGA which the presence of CaC03has been proved at 1600 to 1400 cm-\ and one significant weight lost curve at 600 until 800°C with the total weight loss of the sample was 39.85%. Soil pH has been determined by using calcium chloride (CaCl2) and distilled water first before CaC03 being applied on each sample. After taking all the pH of each sample, CaC03 were introduced on each sample to study the effect of CaC03 on soil pH. In this study, 10% to 50% of weight of CaC03 has been applied on each sample and based on the results that has been obtained, 50% weight of CaC03 that has been applied was chosen as the best among the other four percentage due to its effect that having results of pH reach seven and consider as neutral when being tested with both calcium chloride and distilled water